(3MGTjI Ydi TQM edNU GdLZejfi dbGVi RGOg GdQheis - (3YHO GdYdj Hf eMeO Hf MSjf GdHQLfOj GdMfaj,J (B932 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdeTGQb hGdeZGQH hHYO , agPg JYdjbGJ Ydi GdehGVY GdeTcdI, hJfHjgGJ Ydi GdQehR hGdeHGMK GdNajI GdeYVdI ef TQM GdedNU ai GdgjFI GdefThH GdeTJgQ HGdbGVi GdQhei s
(3BNQgG (B:s
(3hGdTgQ GdTeSi GdMbjbi bO jRjO Ydjg , hbO jSGhjg , hbO jfbU Yfg hGddg CYde HGdUhGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B3s
(3HgG fXGe GdJYbjHIs
(3cJHJ Hbde eged GdfbW CMjGfkG bdjdIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B172 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B586s
Keywords: (3Gdadcs